2007
DOI: 10.1016/j.jbiomech.2007.01.021
|View full text |Cite
|
Sign up to set email alerts
|

Effects of implant design parameters on fluid convection, potentiating third-body debris ingress into the bearing surface during THA impingement/subluxation

Abstract: Aseptic loosening from polyethylene wear debris is the leading cause of failure for metal-on-polyethylene total hip implants. Third-body debris ingress to the bearing space results in femoral head roughening and acceleration of polyethylene wear. How third-body particles manage to enter the bearing space between the closely conforming articulating surfaces of the joint is not well understood. We hypothesize that one such mechanism is from convective fluid transport during subluxation of the total hip joint. To… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 13 publications
2
15
0
Order By: Relevance
“…The present hip simulator experiment convincingly demonstrated that subluxation facilitates third body particle entry into the bearing space, and it provides physical confirmation of the results of related computational fluid dynamics (Lundberg et al, 2007b) and retrieval (Lundberg et al, 2007a) studies. Debris embedded in the acetabular liner at wear-critical locations subsequently scratches the femoral head, which can lead to increased wear of the acetabular liner.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The present hip simulator experiment convincingly demonstrated that subluxation facilitates third body particle entry into the bearing space, and it provides physical confirmation of the results of related computational fluid dynamics (Lundberg et al, 2007b) and retrieval (Lundberg et al, 2007a) studies. Debris embedded in the acetabular liner at wear-critical locations subsequently scratches the femoral head, which can lead to increased wear of the acetabular liner.…”
Section: Discussionsupporting
confidence: 84%
“…Subluxation is presumably a commonplace occurrence in THA, as retrieval studies have documented a high prevalence of damage (up to 66% of specimens) on the rim of acetabular liners, indicative of femoral neck impingement (Hall et al, 1998;Isaac et al, 1992;Jasty et al, 1997;Murray, 1992;Shon et al, 2005;Wroblewski, 1985;Yamaguchi et al, 2000;Yamaguchi et al, 1999). A recent computational fluid dynamics model has provided theoretical evidence that, during THA subluxation, joint fluid is actively drawn into the space that opens between the head and liner (Lundberg et al, 2007b), providing access to wear-critical regions of the bearing surface near the pole of the liner. Third body particles suspended in this fluid would presumably be convected into the articulating surfaces by this mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…However, wear rates of components retrieved at revision THA tend to be higher than those derived from primary cases, with average values of 94 and 99 mm 3 /year reported in previous series [20,48]. This increase may be the result of the occurrence of repetitive microseparation with rim impingement and the presence of third-body particles, either within the joint fluid or embedded within the articular surface [36,41].…”
Section: Discussionmentioning
confidence: 93%
“…The data showed the patients who had cable-implantation have fared dramatically worse by virtually all measures associated with wear/osteolysis/loosening. The prevalence of proximal femoral osteolysis was 1.66 times as high (47.4% versus 28.6%; chi square p \ 0.0001), the prevalence of acetabular osteolysis was 2.25 times as high (21.4% versus 9.5%; chi square p \ 0.0003), the mean linear radiographic wear rate was 23 implant survivorship for the patients with third-bodychallenge was worse (p \ 0.026) and becoming increasingly more so (Fig. 14).…”
Section: Quantitative Studies Of Third-body Wear Accelerationmentioning
confidence: 98%
“…To test this hypothesis [23], a three-dimensional computational fluid dynamics (CFD) model was developed and physically validated to quantify fluid ingress into the bearing space during subluxation events. The physical validation (error \ 15%) was performed using particle image velocimetry (PIV), a technique by which motions of reflective, neutrally buoyant micromarkers dispersed in the fluid are tracked and their velocities measured.…”
Section: Quantitative Studies Of Third-body Wear Accelerationmentioning
confidence: 99%